Bisagra urbana (2017)
Bisagra Urbanas' principal purpose was to find a place in the city which had a close relationship with the future metro and that had great potential for generating architecture. The chosen spot was Barrio Santa Fé which is located at the entrance of the traditional center of Bogotá. One of the main reasons which drove me to this specific place was the fact that the city has been trying to develop, approximately since 10 years, a project that becomes the perfect example between urban renovation and mobility. During the analysis I found the project of Central Station. IDU and ERU were working together with the objective of designing a station that connected the TransMilenios' lines of Cra. 10ma and Av. Caracas. This project named Central Station became an opportunity to transform this place into a connection center vital to the city and an entrance worthy of the traditional center. I decided to re-design Sector 3 of the Central Station project according to the new means of mass transportation. Located between streets 24 and 26 and Avenues 14 and 17, the project had 1.7 ha. One of the main tools which was very important for the analysis was the one of the topographic map in which I had the evidence to prove that there were two different cities which had no connection whatsoever at urban scale. The second tool I used was the booklet of Observatorio de Vivienda of Universidad de los Andes which worked as a base and guide to the project. The idea of designing the project as a door to the traditional center was the basis for the projection of one tower and two bars which created an urban site.The essential ideas of the project were the conservation of the original urban trace, the preservation of historic buildings and the revival of the place through means of design. The connections and encounters at different levels, the resolution of borders and the design of a new image for a place that has been forgotten were some of the main points for Bisagra Urbana.--Tomado del Formato de Documento de Grado.